Building the "contraption": anti-austerity movements and political alternative in Portugal - Estanque, Elísio (2018)
The cycle of anti-austerity contention between 2010 and 2013 in Portugal reveals a complex picture, where traditional actors, including trade unions and left-wing political parties, emerged as key actors. This gave rise to a period of intense polemics in the political arena, since the former right-wing majority refused to accept a new Prime Minister (António Costa, the leader of Socialist Party) who “lost” elections in late 2015. However, a “defeated” leader achieved power and was able to draw the “square of the circle”, negotiating and forging agreements among the divided forces of the Left. This government solution, because of its supposed fragility and lack of consistency, became known as the “Contraption” (“Geringonça”, in Portuguese). But more than a year later it still resisted and could even avoid some difficult obstacles.